The Impact of Female Executives’ Proportion on Corporate Performance – Evidence from China’s Garment Industry - Shi, Junchi; Wu, Maoguo (European Scientific Journal, ESJ, 2018)
With the global appeal on gender equality, female executives’ proportion in corporations has become higher and higher. As an industry closely related to the female, is the corporate performance of the garment industry influenced by female executives’ proportion? This paper attempts to answer this question by empirical testing the impact of female executives’ proportion on the corporate performance of China’s garment industry. It investigates 20 listed Chinese garment firms from 2007 to 2015. Female executives’ proportion, along with company size, current asset turnover ratio, asset-liability ratio, number of employees, staff costs, ratio of inventory to current assets, ratio of accounts receivable to current assets, number of board meetings, and net profit growth rate, is tested to analyze the relation between female executives’ proportion and corporate performance. Fixed effect (FE) model, pooled ordinary least square (pooled OLS) model, and panel corrected standard errors (PCSE) model are utilized for robustness check. Empirical results find that female executives’ proportion has a negative impact on the corporate performance of China’s garment industry. Although the female has more of connection with the garment industry, higher female executives’ proportion does not necessarily bring better corporate performance.